PENGARUH KEDISIPLINAN, KEPEMIMPINAN KEPALA SEKOLAH, LINGKUNGAN, DAN METODE PEMBELAJARAN TERHADAP PRESTASI SISWA DI SMAN 1 SUNGGUMINASA - Dewi Rezki H; Hasmin Tamsah (Jurnal Mirai Management, 2016)
Abstract This research aims: 1) To analyze the effect of discipline on student achievement at SMA Negeri 1 Sungguminasa. 2) To analyze the impact of school leadership on student achievement at SMA Negeri 1 Sungguminasa. 3) To analyze the influence of the school environment on student achievement at SMA Negeri 1 Sungguminasa. 4) To analyze the effect of teaching methods on student achievement at SMA Negeri 1 Sungguminasa. 5) To analyze the influence of discipline, school leadership, environment and learning methods simultaneously on student achievement at SMA Negeri 1 Sungguminas. The research location is at State Senior High School (SMA) 1 Sungguminasa. The population in this study is the overall teacher status of Civil Servants SMA Negeri 1 Sungguminasa total of 37 people. Sampling by using census population taken as a whole.For testing the hypothesis with multiple regression analysis. The results showed that: 1) Discipline teacher positive and significant impact on student achievement SMA Negeri 1 Sungguminasa Gowa Makassar. 2) Leadership principals positive and significant impact on student achievement SMA Negeri 1 Sungguminasa Gowa Makassar. 3) The school environment is positive and significant impact on student achievement SMA Negeri 1 Sungguminasa Gowa Makassar. 4) Method of learning positive and significant impact on student achievement SMA Negeri 1 Sungguminasa Gowa Makassar. 5) Discipline, Leadership Principal, Environmental, and learning methods simultaneously positive and significant impact on student achievement in high school (SMA) Negeri 1 Sungguminasa Gowa.Keywords: Discipline, Leadership Principal, Environmental, and methods oflearning, Student Achievement